2019
DOI: 10.1038/s41598-019-52730-4
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immunogenicity and Efficacy of a Single Dose of ChAdOx1 MERS Vaccine Candidate in Dromedary Camels

Abstract: MERS-CoV seronegative and seropositive camels received a single intramuscular dose of ChAdOx1 MERS, a replication-deficient adenoviral vectored vaccine expressing MERS-CoV spike protein, with further groups receiving control vaccinations. Infectious camels with active naturally acquired MERS-CoV infection, were co-housed with the vaccinated camels at a ratio of 1:2 (infected:vaccinated); nasal discharge and virus titres were monitored for 14 days. Overall, the vaccination reduced virus shedding and nasal disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
102
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 47 publications
(50 reference statements)
6
102
0
2
Order By: Relevance
“…Although Ad41-S induced humoral immunity in serum, it was significantly less than Ad5-S (39). Chimpanzee adenovirus-based vector systems have also been used (40). In our work, we demonstrated that a single dose as low as 10 4 PFU of PIV5-MERS-S was sufficient to provide 100% protection against lethal MERS-CoV challenge.…”
Section: Discussionmentioning
confidence: 66%
“…Although Ad41-S induced humoral immunity in serum, it was significantly less than Ad5-S (39). Chimpanzee adenovirus-based vector systems have also been used (40). In our work, we demonstrated that a single dose as low as 10 4 PFU of PIV5-MERS-S was sufficient to provide 100% protection against lethal MERS-CoV challenge.…”
Section: Discussionmentioning
confidence: 66%
“…A good number of these articles were published in high-quality medical and scientific journals and covered both translational and clinical research. Saudi Arabia has started its first ever phase I clinical trial on a vaccine candidate for MERS-CoV (Clinical trial NCT04170829); The MIRACLE trial has started and been ongoing to evaluate antiviral therapeutics in severely infected MERS patients (Clinical trial NCT02845843) and now will include COVID-19 patients, and two vaccines have been developed and tested in animal studies [33,34]; another vaccine has been tested in camels as a one-health veterinary vaccine, since camels are the intermediate host for MERS-CoV [35], in addition to several epidemiologic and observational studies.…”
Section: Mers Emergence and Lesson Learnedmentioning
confidence: 99%
“…Following 48 h incubation, cells were lysed and the assay was developed using Bright-Glo™ Luciferase Assay System (Promega, USA) and luciferase activity was measured using a luminometer. 50% of inhibitory concentration (IC50) neutralization titers (in Log10) were calculated for each serum sample using GraphPad Prism (25).…”
Section: Mers Pseudotyped Viral Particles (Merspp) Neutralization Assaymentioning
confidence: 99%